Effectiveness and safety of Chinese herbal medicine xuanbi antong granules for the treatment of borderline coronary lesions: study protocol for a randomised, double-blinded, placebo-controlled, multicentre clinical trial. Issue 8 (8th August 2019) - Huang, Mingyan; Chen, Guang; Guan, Qingya; Liu, Chao; Zhao, Qing; Li, Jun; Yao, Kuiwu; Zhang, Zhenpeng; He, Haoqiang; Li, Yi; Lin, Fei; He, Xinhui; et al.
Abstract : Introduction: As the early stage of coronary heart disease (CHD), borderline coronary lesion (BCL) is defined as a 30%–70% diameter stenosis. Previous studies have demonstrated that BCL may progress to acute coronary syndrome easily. However, routine medications available for the treatments of BCL have some limitations. Xuanbi antong granule (XAG) has been used for the treatment of BCL in China for many years. Previous studies have shown that XAG has effectiveness in improving clinical symptoms and quality of life in patients with CHD. This study aims to evaluate the effectiveness and safety of XAG in patients with BCL. Methods and analysis: This is a multicentre, randomised, double-blinded, placebo-controlled clinical trial. A total of 300 participants will be randomly assigned to the intervention group and the placebo group. Based on routine medications, the intervention group will be treated with XAG and the placebo group will be treated with XAG placebo. All participants will receive a 6-month treatment and then be followed-up for another 6 months. The primary outcomes are the changes of target plaque characteristics (including target plaque volume, degree of stenosis, CT value and calcification score) measured by dual source CT angiography. The secondary outcomes include blood lipid indicators, efficacy of angina symptoms, Seattle Angina Questionnaire, high-sensitivity C-reactive protein and occurrence of major adverse cardiac events. All the data will be recorded in electronic case report forms and analysed by SPSS V.20.0. Ethics and dissemination: This study has been approved by Research Ethics Committee of Guang'anmen Hospital, China Academy of Chinese Medical Sciences in Beijing, China (No. 2017–083-KY-01). Written informed consent will be obtained from all participants. The results of this study will be disseminated to the public through academic conferences and peer-reviewed journals. Trial registration number: ChiCTR-IOR-17013189; Pre-results.